Analisis Determinan Pertumbuhan Ekonomi Di Indonesia Tahun 2000-2021 - Ayu Kania Azzahra, Akalili; Soebagyo, Daryono (Fakultas Ekonomi Universitas Gresik, 2023)
This research aims to determine the effect of foreign debt, foreign investment, interest rates, and exchange rates on economic growth in Indonesia in the 2000-2021 period. The data used in this research is a time series using a multiple regression analysis tool model with the Partial Adjustment Model (PAM) approach. The results obtained in this research are that the foreign debt variable has a positive and significant effect on economic growth in Indonesia. The foreign investment variable has a significant negative effect on economic growth in Indonesia in the 2000-2021 period. Meanwhile, the interest rate and exchange rate variables did not yield significant results for economic growth in the 2000-2021 period.